Sex differences in the association of phase angle and lung cancer mortality - Shi, Jinyu; Xie, Hailun; Ruan, Guotian; Ge, Yizhong; Lin, Shiqi; Zhang, Heyang; Zheng, Xin; Liu, Chen’an; Song, Mengmeng; Liu, Tong; Zhang, Xiaowei; Yang, Ming; et al. (Frontiers in Nutrition, 2022)
Background Lung cancer is a lethal malignant tumor that is common worldwide and is associated with a high incidence of malnutrition. Phase angle (PA) is a simple, objective, and non-invasive indicator of body composition that has increasingly attracted attention as an indicator of the nutritional status and prognosis of patients with malignant tumors. This study aimed to investigate the association between the PA and overall survival in patients with lung cancer. Methods This study prospectively analyzed 804 lung cancer patients in the Investigation on Nutrition Status and its Clinical Outcome of Common Cancers (INSCOC) project from 40 hospitals in China. We used a restricted cubic spline to analyze the sex-specific association between PA and mortality in men and women with lung cancer. Cox regression analysis was used to evaluate the independent association between PA and mortality in men and women. Sensitivity analysis was performed. The Kaplan–Meier method was used to evaluate the survival of patients with high and low PA values. Results There was an L-shaped association between PA and survival in both men and women with lung cancer (p = 0.019 and p = 0.121, respectively). Kaplan–Meier survival analysis suggested that patients with a high PA showed a better survival than patients with a low PA (p = 0.007 for men and p < 0.001 for women). Multivariate-adjusted Cox regression analysis showed that PA was an independent risk factor for mortality in men (HR = 0.79, 95% CI = 0.65–0.95, p = 0.015), but not in women (HR = 0.83, 95% CI = 0.67–1.04, p = 0.105). Conclusion Phase angle is an independent risk factor for the mortality of male lung cancer patients. However, its role in predicting the mortality of female lung cancer patients seems to be limited.